PENGARUH PROFITABILITAS PERUSAHAAN SOLVABILITAS, DAN FAKTOR LAINNYA TERHADAP AUDIT DELAY - RUDI SETIADI TJAHONO; VELIA FINDRIANI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to analyze and get to know empirically the influence of company profitability, solvability, company size, audit opinion, public accounting firm's size, audit tenure, audit committee, and liquidity to audit delay. Sample in this research are non-financial companies listed in Indonesian Stock Exchange with research period from 2017 until 2019 and the sampling method used in this research is purposive sampling method. There were 165 companies that meet the criteria and chosen as the samples and with a total of 495 samples used. This research used multiple regression analysis.The result of this study identified that profitability, company size, audit opinion, had negative effect on audit delay, while solvability, Public Accounting Firm's Size, audit tenure, audit committee, and liquidity to audit delay had no influence on Audit Delay